174k views
4 votes
Solving systems of equations algebraically.

y = 4x - 9
y= x - 3
And SHOW YOUR WORK PLEASE!!!!

1 Answer

4 votes

Answer:

x = 2

y = -1

Explanation:

Since it gives you the value of y already, just plug that into the equation, like so:

y = 4x - 9

x - 3 = 4x - 9

Subtract the x from both sides:

x - 3 = 4x - 9

-x - x

__________

-3 = 3x - 9

Then, add 9 to both sides:

-3 = 3x - 9

+9 + 9

________

6 = 3x

Divide both sides by 3:

2 = x

Now plug in x for y:

y = x - 3

y = 2 - 3

y = -1

User XpressGeek
by
4.6k points